Between Night and Night - Bonny Cassidy (2020)
Background: This review essay discusses the Australian poet, Peter Boyle, in the contexts of the long poem and ecopoetics. It considers how Boyle’s poetics demonstrates the impact of his late partner, anthropologist Deborah Bird Rose. This essay engages with my substantial record of scholarly and critical publications of Australian poetry and ecocriticism, as well as my creative practice as the author of a book-length poem, Final Theory (2014) concerned cosmology and colonisation. Contribution: In ‘Between Night and Night’ I use the review essay to make a transdisciplinary link between Boyle’s recent book-length poem, Enfolded in the Wings of a Great Darkness, and work of Bird Rose by incorporating images from her writing as well as concepts of animism. Since other reviews of Boyle’s works associate him with French, Spanish and Latin American surrealism and metafictional voice, this is a new way of approaching Boyle’s work. It also adds to discourse on the interplay between First Nations philosophy and non-Indigenous Australian poetics. Bird Rose’s influence on Australian poetics has been documented in Australian literary scholarship, however this essay brings the transdisciplinary discourse into a more accessible field of arts criticism. I reinforce this effect by referencing my own creative practice and autobiography, to invite the reader to consider extra-literary influence. Significance: Since publication I have received two unsolicited emails praising the essay for its “criticism that went deeply into things.” Sydney Review of Books is Australia’s leading source of extensive literary criticism. My review was commissioned by the editor, and the publication is guided by an editorial advisory board of high-profile peers. This commission has been echoed by recent invitations to publish leading chapters in scholarly collections from Palgrave and Cambridge University Press. The journal is a free online publication, ensuring high impact through global access.